Oxford Scholarship Online 2017
DOI: 10.1093/acprof:oso/9780199346677.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

The role and significance of masterclasses in creative learning

Abstract: Masterclasses have a prominent place in the education of future musicians within the western classical music tradition. This chapter gives an overview of research on teaching and learning in masterclasses with a focus on how they might benefit the students, as well as how master teachers and students can optimize learning and teaching outcomes. The merits of various types and formats of masterclass and styles of interaction are discussed, as are the challenges faced by master teachers and student performers. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The present research explored the verbal descriptions and reflections of participants who enrolled to a group, online course based on creativity, movement, and collaboration. As such, this work complements other studies that focus on the transition between face-to-face and remote learning (e.g., Camlin and Lisboa, 2021 ; Ritchie and Sharpe, 2021 ), on online music lessons offered to more skilled participants (e.g., Johnson, 2017 ), and on forms of musical learning based on imitation and the reproduction of scores ( Lisboa et al, 2005 ; Hanken, 2017 ). To achieve our objective, we asked four novices to participate in a 12-week, newly designed music course delivered remotely from the start and conducted two semi-structured interviews with each learner after 1 month and 3 months from the beginning of the course.…”
Section: Discussionsupporting
confidence: 54%
“…The present research explored the verbal descriptions and reflections of participants who enrolled to a group, online course based on creativity, movement, and collaboration. As such, this work complements other studies that focus on the transition between face-to-face and remote learning (e.g., Camlin and Lisboa, 2021 ; Ritchie and Sharpe, 2021 ), on online music lessons offered to more skilled participants (e.g., Johnson, 2017 ), and on forms of musical learning based on imitation and the reproduction of scores ( Lisboa et al, 2005 ; Hanken, 2017 ). To achieve our objective, we asked four novices to participate in a 12-week, newly designed music course delivered remotely from the start and conducted two semi-structured interviews with each learner after 1 month and 3 months from the beginning of the course.…”
Section: Discussionsupporting
confidence: 54%
“…Masterclasses engender intense and highly focused learning environments (Atkinson et al, 2013) in which, in the presence of an audience, a student performer is observed, coached, and given spontaneous critical feedback on their musical performance by someone deemed "expert" in a specific skill area. In a particularly successful masterclass, learning occurs both for the student, for whom a certain, often very high, level of competence in their specialization is expected to have already been achieved, and for members of the audience (Haddon, 2014;Hanken, 2010Hanken, , 2015Hanken, , 2017, many of whom are also likely to be musicians at various stages of their development.…”
Section: Music Learning and Discoursementioning
confidence: 99%
“…Musical pedagogy for learning traditional Western musical instruments is currently most often delivered in one-on-one or group contexts through a master-apprentice model, typically one time per week for 30–60 min per session (Hanken, 2017 ). Between those meetings, students practice on their own the assigned exercises and, attempting to apply the suggestions received in class, try to reach the learning goals set out by the instructor.…”
Section: Introductionmentioning
confidence: 99%